PENGARUH PENERAPAN PEMBELAJARAN KOOPERATIF TIPE STAD TERHADAP KEMAMPUAN PEMECAHAN MASALAH MATEMATIKA - NURUL AULIA DEWI; MUHAMMAD IRHAM; SARWO EDY WIBOWO (Universitas Mahasaraswati Mataram, 2021)
This study aims to determine the effect of the Type STAD Cooperative Learning model on mathematical problem solving abilities. The data collection technique was obtained by means of a test in the form of description questions and documentation in the form of a list of student names. The research instrument used was 3 pre-test and post-test questions. The data analysis technique used is the normality test, homogeneity, t test with the technique of paired samples t-test and independent t-test. The results showed that, the paired sample t-test on the problem solving ability before and after treatment with STAD obtained an average value of 50.29 to 83.71 with a significance of 0.000 <0.05. This means that the students' scores before and after STAD learning have differences in the average mathematical problem solving abilities. Based on the results of the paired sample t-test on the ability to solve mathematical problems before and after treatment using conventional learning models, the average value was 44.57 to 75.79 with a significance of 0.000 <0.05. This means that there is a significant increase before and after conventional learning. Based on the results of the independent samples t-test, the mean values were 83.71 and 75.79 with a significance value of 0.009 <0.05. This means that there is a difference in the average problem-solving ability of students in STAD learning with students in conventional learning. It can be concluded that the STAD type of cooperative learning model has an effect on students' problem solving abilities in mathematics.